The Quack's Daughter : A True Story about the Private Life of a Victorian College Girl, Revised Edition - Nettleton, Greta, 1957- (Book collections on Project MUSE., 2014)
Raised in the gritty Mississippi River town of Davenport, Iowa, Cora Keck could have walked straight out of a Susan Glaspell story. When Cora was sent to Vassar College in the fall of 1884, she was a typical unmotivated, newly rich party girl. Her improbable educational opportunity at "the first great educational institution for womankind" turned into an enthralling journey of self-discovery as she struggled to meet the high standards in Vassar's School of Music while trying to shed her reputation as the daughter of a notorious quack and self-made millionaire: Mrs. Dr. Rebecca J. Keck, second